Skilled WorkforceTrainingin the South of Ukraine in the Second Half оf XIX– early XX centuries: Historiography Question - Mykhayilo Honchar (Pedagogical Discourse, 2013)
The results of dissertation research for the degree of candidate and doctor of science in pedagogy and history  which weredefended in Ukraine in late XX - early XXI centuries and outline theskilled workforce training in the South of Ukraine in the second half of XIX – early XX centuries have been analyzed. It was found that this question was partially reflected in the present historical and historical-pedagogical scientific search. The analyzed scientific researches donʼt provide a clear understanding of how the qualified personnel for actual Southern Ukraine industries were prepared, and what organizational and pedagogical features were typical for different types of lower vocational schools.